Donor-derived cell-free DNA as a diagnostic tool in transplantation - Oellerich, Michael; Budde, Klemens; Osmanodja, Bilgin; Bornemann-Kolatzki, Kirsten; Beck, Julia; Schütz, Ekkehard; Walson, Philip D. (Frontiers in Genetics, 2022)
There is a need to improve personalized immunosuppression in organ transplantation to reduce premature graft loss. Biomarkers are needed to better detect rejection, asymptomatic graft injury, and under-immunosuppression. Assessment of minimal necessary exposure to guide tapering and prevent immune activation is also important. There is robust clinical evidence from a large number of published studies supporting the role of dd-cfDNA for monitoring graft integrity and detection or exclusion of rejection. Dd-cfDNA indicates graft cell death without being rejection specific. It can be determined in plasma through droplet digital PCR or next generation sequencing. Changes in recipient cfDNA (e.g. by infection) can affect the results of dd-cfDNA fractional determination. This limitation can be overcome using absolute dd-cfDNA quantification. The combination of fractional and absolute determination including total cfDNA is recommended for meaningful interpretation of the results. The value proposition for the patient includes earlier transplant injury detection and intervention, less full blown rejection risk, an alternative to invasive biopsies, and personalized immunosuppression with potential for improved long-term outcome. Transplant physicians benefit from better immunosuppressive guidance and having an alternative when biopsies are refused or contraindicated. Further advantages are improved biopsy interpretation, less trial and error changes in immunosuppression, and less time dealing with complications. The laboratory medicine specialist can provide more effective services. Hospital management and insurance companies could benefit from more cost-effective surveillance of transplant recipients. Potential cost savings would result from fewer biopsies as a result of the tests’ high negative predictive value, fewer re-transplantations, and less organ failure with return to dialysis. A pathway to implementation and metrics is suggested to measure the effectiveness of dd-cfDNA testing.